Smart Assistant for Deaf and Mute Using Micro:bit - Alasaad, Entesar (PROtek : Jurnal Ilmiah Teknik Elektro, 2025)
Deaf and mute people are an integral part of society. They have difficulty speaking or are unable to speak. Therefore, to overcome this difficulty, sign language emerged as a method of non-verbal communication commonly used by deaf and mute people. The problem that arises with sign language is that healthy people who do not suffer from hearing or speaking problems do not learn this language. This problem is dangerous because it creates a barrier between them. It is possible to solve this problem by taking advantage of modern technologies as they are more applicable and cheaper. In this research, the micro:bit was used as a means aimed at facilitating communication between deaf and mute people and other people through human-computer interaction. A program has been created that transforms what a mute wants into luminous expressive forms that can be easily understood by healthy people, such as his desire to eat or drink or any other needs. Another important point is to alert the deaf person to the presence of an external sound (car alarm, someone calling to the deaf person, etc.) by lighting up the micro:bit. The micro:bit is easy to use and low-cost. It was also improved by being developed into a watch worn by a disabled person. This device is expected to support deaf and mute people (especially children) in communicating effectively with others and regaining a sense of normalcy in their daily lives. This research idea was applied to a sample of ten deaf and mute children of different ages ranging from (2-10 years) after training them on how to use the program represented by the manual watch. It was noted that children under the age of six (4 children) benefited more than others, because children over 6 years old are able to express their needs and meet them compared to younger children.